Alternative education and social justice: considering issues of affective and contributive justice. Issue 1 (2nd January 2016) - Mills, Martin; McGregor, Glenda; Baroutsis, Aspa; Te Riele, Kitty; Hayes, Debra
Abstract : This article considers the ways in which three alternative education sites in Australia support socially just education for their students and how injustice is addressed within these schools. The article begins with recognition of the importance of Nancy Fraser's work to understandings of social justice. It then goes on to argue that her framework is insufficient for understanding the particularly complex set of injustices that are faced by many highly marginalised young people who have rejected or been rejected by mainstream education systems. We argue here for the need to consider the importance of 'affective' and 'contributive' aspects of justice in schools. Using interview data from the alternative schools, we highlight issues of affective justice raised by students in relation to their educational journeys, as well as foregrounding teachers' affective work in schools. We also consider curricular choices and pedagogical practices in respect of matters of contributive justice. Our contention is that the affective and contributive fields are central to the achievement of social justice for the young people attending these sites. Whilst mainstream schools are not the focus of this article, we suggest that the lessons here have salience for all forms of schooling.